Approximate controllability of semi-linear stochastic integrodifferential system with multiple delays and Poisson jumps in control. Issue 3 (3rd April 2023) - Annamalai, Anguraj; Kasinathan, Ravikumar; Kasinathan, Ramkumar
Abstract : The objective of this paper is to interpret the approximate controllability of a semi-linear stochastic integrodifferential system with multiple delays and Poisson jumps in control in infinite-dimensional spaces. Sufficient conditions for the approximate controllability of semi-linear control system have been established. The results are obtained using the Banach fixed point theorem and the theory of resolvent operator developed in Grimmer [ Resolvent operator for integral equations in Banach spaces, Trans. Am. Math. Soc. 273 (1982), pp. 333– 349.]. An example is introduced to show the effectiveness of the result.